Exploring the Impact of covid COVID-19 Lockdown on Human Resource Management in the Gauteng Office of the Premier - Masango, Bheki (University of the Witwatersrand, Johannesburg, 2024)
The literature regarding the global pandemic of Covid-19 and its disruption to life in 2020 continues to grow and develop. This study investigated the impact of Covid-19 has had on Human Resource Practitioners, the human resource practices and the impacts of the decision making process for various the public sector. The purpose of this study was to develop an understanding of how the global pandemic has changed the roles of human resource practitioners and what future implications may result from the global pandemic. This investigation required a thorough analysis of their lived experiences regarding their roles as practitioners in the human resources field prior to the global pandemic and during the pandemic. This qualitative study employed a narrative research method, with a theoretical framework focusing institutional theories and theoretical approaches to HRM and Crisis research to provide a comprehensive overview of the literature. The purposeful sample consisted of 15 human resources practitioners who were presently employed in human resource departments in the Gauteng Office of the Premier. The participants all resided in Gauteng province. The researcher conducted a questionnaire with 5 of the participants, followed by followed by a 45- to 60-minute semi-structured one-on-one interview with the remaining 10 participants. Data analysis employed ATLAS ti. software analysis which led to a thematic analysis. After coding, five themes were identified describing the participants’ five key influencers from the effects of Covid-19 on human resources systems and practitioners. Four conclusions emerged from this study. Human Resource Practitioners will have a more active role in if not lead in crisis management, Organisational Leadership will rely heavily on Human Resource Practitioners in the decision making process for all future crisis, disaster, and pandemic responses, Human Resource practitioners will develop new policies in regard to changes made due to Covid-19 disruptions.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; workplace changes; technical assistance; implementing remote work practices; employee remote work experience; organisational support initiatives; and professional and personal issues; SDG-3: Good health and well-being